DLQI and POSAS scores in keloid patients - Pötschke, Julian; Reinholz, Markus; Schwaiger, Hannah; Epple, Andreas; Gauglitz, Gerd (Facial plastic surgery, 2016)
The treatment of keloids remains complex and challenging. A multitude of different treatment options exists. While current guidelines frequently promote the combination of intralesional triamcinolone acetonide (TAC) and cryotherapy as a first-line therapy for keloids, its efficacy has mainly been proven clinically and objective evaluation is widely missing. Here, we aimed to evaluate the efficacy of TAC and cryotherapy for the improvement of keloids by employing two well-recognized questionnaires for the evaluation of scar appearance and patient's quality of life. Twenty keloid patients from our outpatient scar clinic were treated with individual doses of TAC and cryotherapy in four consecutive sessions. Retrospectively, Patient and Observer Scar Assessment Scale (POSAS) and Dermatology Life Quality Index (DLQI) questionnaire data from those patients were analyzed to evaluate changes over five visits (one baseline, four after treatment). Both overall patient and observer scores of the POSAS significantly decreased (41.10 ± 9.771 to 29.85 ± 11.42 [p p < 0.001], respectively), while DLQI scores significantly declined over the time period studied, indicating significant improvements in scar appearance. Objective evaluation confirmed the clinically demonstrated improvements of scar appearance and symptoms after treatments with TAC and cryotherapy which was associated with significant improvements in quality of life as indicated by DLQI measures. Standardized questionnaires help in objectifying clinical improvements; however, more detailed options for scar documentation, such as objective imaging, may be additionally required for an in-depth analysis of treatment progress.
Gesehen am 03.11.2020